STRESS DISTRIBUTION ANALYSIS ON LIGAMENT AUGMENTATION AND RECONSTRUCTION SYSTEM (LARS) USING FINITE ELEMENT METHOD (FEM) - Aulia , Fauzan; Sonief, Achmad As’ad; Hidayati , Nafisah Arina (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
The Ligament Augmentation and Reconstruction System (LARS) is a prosthetic device used to support knee ligaments severed due to injury. The role of LARS in supporting the knee ligaments is to take over the position of the natural ligaments that have been severed, binding the thigh bone and shin bone. LARS is made from polyethylene terephthalate (PET) material, commonly used in industry. LARS is a prosthetic product widely used to heal ligament injuries. However, despite its everyday use, no one has confirmed whether LARS can support a severed ligament. There has never been a study analyzing this tool, even from the company that makes LARS. They only state that LARS is safe and suitable for healing ligament injuries. Therefore, a LARS analysis is needed to convince the public that the tool is safe. This study analyzed the stress distribution in LARS during the standing-to-squatting condition. The results show an uneven stress distribution between the LARS inside the femur and other parts of the LARS. However, the stress distribution is still in a safe condition that does not directly reduce the strength of the LARS.